(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article delves into the historical foundations of comparative linguistics, tracing its origins from the 18th century to the contemporary era. Beginning with the groundbreaking insights of Sir William Jones, the narrative explores the birth of comparative linguistics and its subsequent development through key figures like Franz Bopp and the Neogrammarians. Emphasizing the Indo-European studies as a catalyst, the article illuminates the evolution of sound laws and the application of the comparative method in deciphering linguistic relationships. The article navigates through challenges and controversies, showcasing the refinement of methods and the impact of technology in the 20th and 21st centuries. Ultimately, it underscores the enduring significance of comparative linguistics in unraveling the intricate tapestry of human language evolution.